Antioxidative metabolism in sugarcane (Poaceae) varieties subjected to water and saline stress - Marciana B. de Morais; Ricardo A. Azevedo; Terezinha R. Camara; Cláudia Ulisses; Cynthia C. de Albuquerque; Lilia Willadino (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to identify the antioxidant responses of sugarcane (Saccharum spp.) varieties subjected to water and saline stress. Sugarcane seedlings of six different varieties obtained through micropropagation were subjected to either water or saline stress, or a combination of water + saline stress. The study was carried out in May 2012, in a greenhouse at the Universidade Federal Rural de Pernambuco (UFRPE). The experimental design was randomized, with treatments arranged in a 6 × 4 factorial scheme (six varieties and four treatments), and four replicates. Lipid peroxidation, hydrogen peroxide (H2O2) concentrations, and relative water content (RWC) were evaluated. Furthermore, we evaluated the plants’ antioxidative defense systems by measuring the activities of superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT). The sugarcane varieties had higher lipid peroxidation and/or higher H2O2 concentrations when subjected to the combined water + saline stress. The antioxidant enzymes responded to the water and saline stress treatments differently depending on the sugarcane variety. However, under combined saline + water stress conditions, the enzymes may have become inactivated, which indicates that the response to the combined water + saline stress was different from the sum of the responses to only water stress or only saline stress. High concentrations of malondialdehyde (MDA) associated with low RWC may be an effective indicator of multiple stress sensitivity in sugarcane varieties. The RB99395 and RB867515 sugarcane varieties responded more efficiently to environmental stress, and maintained their cell water content when subjected to either water or saline stress.